ANALYSIS OF STUDENT MENTAL WORKLOAD USING NASA TASK LOAD INDEX (NASA-TLX) METHOD - Rahmana, Arief; Maharani Suyono, Annisa; Juraida, Anita; Ratnasari, Ima; Endah Wahyuni, Ayu (International Journal of Psychosocial Rehabilitation, 2020)
The growth number of students is a potential for progress in an area. But often, the workload felt by students is above their limits. It can cause a decrease in student performance due to excessive mental workload. One of the learning methods that is applied in almost every campus is e-learning. This study aims to analyze the level of workload at a university based on the measurement of mental load, especially when working in e-learning platform. The method used is to measure the mental workload with the NASA Task Load Index (NASA-TLX) method. The study was conducted on 40 students. Based on the results of the study, the NASA-TLX score obtained was 65. This indicates that the level of mental burden perceived by students is moderate.